Effects of tropical fruit blends on fermentative and pigmentation aspects of probiotic native cultured goat milk - Isadora Kaline Camelo Pires de Oliveira Galdino; Gabriel Monteiro da Silva; Miqueas Oliveira Morais da Silva; Giordanni Cabral Dantas; Elainy Virgínia dos Santos Pereira; Tiago Almeida de Oliveira; Karina Maria Olbrich dos Santos; Antonio Silvio do Egito; Flávia Carolina Alonso Buriti; Haíssa Roberta Cardarelli (PeerJ)
Background Fruits are sources of bioactive compounds such as phenolics that bring health benefits to consumers. The addition of fruit products and microorganisms with probiotic potential in fermented goat milk can facilitate the acquisition of these benefits through diet. In this sense, the objective of this study was to evaluate the effect of incorporating a mixture of ingredients from jaboticaba (Myrciaria cauliflora), jambolana (Syzygium cumini), and mandacaru (Cereus jamacaru) fruits on fermentation parameters (pH, titratable acidity, viability of the native culture Lactiplantibacillus plantarum CNPC003 and the starter culture), associated with pigmentation (phenolic compound content and color) through experimental mixture design. Methods A simplex-centroid experimental design was conducted, comprised of seven trials totaling the addition of 30% of the fruit preparations in the final formulation of fermented milk and one control trial (without addition of preparations), with the response being the total phenolic content and the instrumental color parameter a*. Fermentations were carried out with the addition of the native culture Lactiplantibacillus plantarum CNPC003 and the starter culture Streptococcus thermophilus. Subsequently, analyses of pH, titratable acidity, viability of the native and starter cultures, total phenolic compound content, and the instrumental color parameter a* were performed. Results The final pH among trials ranged from 4.55 to 4.69, titratable acidity ranged from 0.59 to 0.64, the population of L. plantarum CNPC003 reached levels exceeding 8 log CFU/g, as did the population of Streptococcus thermophilus. The content of phenolic compounds was higher in trials T1, T5, and T7, as well as the color parameter (a*). The use of experimental mixture design contributed to the development of products with high viability of L. plantarum, high content of phenolic compounds, and a characteristic color of the added fruits, bringing benefits to consumer health.